The Role of Job Satisfaction as Mediator The Effect of Competence and Self Efficacy on Employee Performance - Inavatul Mafrukhah; Vivin Maharani Ekowati (IQTISHODUNA, 2023)
This study aims to determine the influence of competence, self-efficacy, and job satisfaction on employee performance and the role of job satisfaction in mediating competence and self-efficacy on employee performance. This research uses quantitative research. This study's population were CV Dan Cell employees, which amounted to 345. The sample in this study was taken using a simple random sampling technique, calculated using the Slovin formula to produce as many as 78 respondents. Data were collected by using a questionnaire (questionnaire). Data analysis in this study used the Partial Least Square (PLS) approach. The results showed that competence had a significant effect on employee performance, self-efficacy had a significant effect on employee performance, job satisfaction could not mediate the relationship between competence and employee performance, job satisfaction could mediate the relationship between self-efficacy and employee performance, and job satisfaction had a significant effect on employee performance.